Comparative study of abdominal wound dehiscence in continuous versus interrupted fascial closure after emergency midline laparotomy - Bansiwal, Rajesh Kumar; Mittal, Tarun; Sharma, Rajeev; Gupta, Sanjay; Singh, Simrandeep; Abhishek, Kumar; Attri, Ashok Kumar (International Surgery Journal, 2019)
Background: Laparotomy wound dehiscence is still a puzzle for most of the surgeons. Mortality associated with dehiscence has been estimated at 10-30%. Patients undergoing emergency laparotomy suffer from one of these comorbid conditions which are detrimental to healing. In this scenario interrupted suturing has been found to give good strength and have less incidence of wound dehiscence. The objective of the study was to compare the incidence of abdominal wound dehiscence in emergency midline laparotomy. Methods: This study was conducted on 300 consecutive patients undergoing emergency midline laparotomy in the Department of Surgery, Government Medical College and Hospital. Methods group-A: closed by suturing the rectus sheath using polydioxanone suture 1-0 (PDS) in continuous layer suturing method. group-B: closed by suturing the rectus sheath using polydioxanone suture 1-0 in interrupted layer suturing method. Results: The mean age in group A was 40.47 years and 37.47 in group B. In Group A 20.1% patients had burst abdomen and 5.4% in group B. Conclusions: Interrupted closure of abdominal wall fascia is better in emergency laparotomy as compared to continuous closure.